PENGARUH PAJAK HOTEL, PAJAK RESTORAN, DAN PAJAK HIBURAN TERHADAP PENDAPATAN ASLI DAERAH KABUPATEN GARUT - Latipatul Hamdah, Dida Farida; Wahyuni, Resa Sri (LAND JOURNAL, 2024)
This research aims to explore the impact of hotel, restaurant and entertainment taxes on original regional income of Garut Regency during the 2015-2022 period. The data for this research is sourced from the implementation reports hotel, restaurant and entertainment tax submitted by the Garut Regency Regional Revenue Agency. The research adopts a quantitative approach, employing data collection methods such as interviews and documents analysis, while data analysis techniques applied in this study include multiple linear regression analysis, coefficient of determination and hypothesis testing using the F test and t test. Data processing in this study was carried out using the SPSS version 26 for Windows program. The findings of this research reveal that collectively hotel, restaurant and entertainment taxes significantly impact local revenue. However, when examined hotel and entertainment taxes do not have a significant impact on local revenue while restaurant taxes have a significant impact on local revenue.